Roots of a polynomial function
If and
are roots of quadratic equation
Then (x – ) (x – β) = 0
x2 – βx – x +
β = 0
x2 – (β +) x +
β = 0
Given a quadratic equation as
ax2 + bx + c = 0, where a, b, c, are constant
Summary
A quadratic equation is given by
x2 – (sum of factors) x + products of factors = 0
Example
1. Given and β as the roots for 4x2 + 8x + 1 = 0 form an equation whose roots are
2 β and β2
Solution
Sum of roots 2 β + β2
=
β (
+ β)
Products of root are (2 β) (β2
)
=3 β3
= ( β) 3
(2 β) (β2
) = (
β) 3
The given equation can be written as
The required equation is
=0
2. The equation 3x2 – 5 + 1 = 0 has roots and β
a) Find values of
b) Find the values of
Solution
+ β =
and
β =
Roots of cubic equations
If, β,
are roots of a cubic equation then
(x –)(x – β)(x – γ) = 0
(x2 – x – βx +
β) (x – γ) = 0
x3 – γx2 – x2 +
γx – βx2 + βγx +
βx –
βγ = 0
x3 – ( + β + γ) x2 + (
γ+ βγ +
β) x –
βγ = 0
x3 – ( + β + γ) x2 + (
γ + βγ +
β) x –
βγ = 0
Given cubic equation can be written as
ax3 + bx2 + cx + d = 0
Equating coefficients of x2, x and the constant terms
i) + β + γ =
-; sum of roots
ii) γ + βγ +
β =
; sum of products of roots
iii) γβ =
; products of roots
Examples
1. The equation 3x3 + 6x2 – 4x + 7 = 0 has roots, β, γ. Find the equations with roots
a)
Solution
From
x3 – (sum of factors) + (sum of products of factors) – products = 0
X3 – (sum of factors) x2 + (sum of products of products of factors) x – products = 0
From the equation 3x3 + 6x2 – 4x + 7 = 0
2. If the roots of the equation 4x3 + 7x2 – 5x – 1 = 0 are , β and γ find the equation whose roots are
a) + 1, β + 1, γ + 1 b)
2, β2, γ2
Solution
4x3 + 7x2 – 5x – 1 = 0